Ecological vulnerability assessment based on remote sensing ecological index (RSEI): A case of Zhongxian County, Chongqing - Lan, Guoxin; Jiang, Xiaolan; Xu, Denghui; Guo, Xianhua; Wu, Yan; Liu, Yixuan; Yang, Yuzheng (Frontiers in Environmental Science, 2023)
The ecological vulnerability evaluation index was established through greenness (NDVI), humidity (WET), dryness (NDBSI) and heat (LST) indicators, comprehensively evaluate the ecological vulnerability of Zhongxian County of Chongqing in 2002 and 2016 by PCA, and analyze its spatio-temporal evolution. The vulnerability areas of five levels were calculated respectively, and the overall index of ecological vulnerability was also calculated. The index of WET and RSEI show upward trends, while the indexes of NDVI, NDBSI and LST show a certain degree of decline. The overall ecological vulnerability index (EVBI) declines, the change are mainly in mild vulnerable areas and moderate vulnerable areas. And it is mainly transferred to mild vulnerable areas, with a downward trend in moderate vulnerable areas, intensity vulnerable areas and severe vulnerable areas. Furthermore, the new increment of ecological vulnerability grade area concentrate on slightly vulnerable area and slightly vulnerable area from 2002 to 2016, while the transfer amount is mainly moderate vulnerability and intensity vulnerability. The ecological vulnerability of the East and Southwest was higher than the middle and Southeast. In general, the ecological vulnerability gradually shifts to low vulnerability, and the ecological environment tends to develop healthily.